2015
DOI: 10.1089/nat.2015.0533
|View full text |Cite
|
Sign up to set email alerts
|

Design and Structural Requirements of the Potent and Safe TLR-9 Agonistic Immunomodulator MGN1703

Abstract: Single-stranded oligodeoxynucleotides (ODN), containing nonmethylated cytosine–guanine motifs (CpG ODN), are recognized by the innate immune system as “danger signals.” CpG ODN are efficacious immunomodulators but require phosphorothioate (PT) or other backbone modifications for metabolic stability, which cause toxicities in mice and primates. We therefore designed a covalently closed DNA molecule (dSLIM®) where two single-stranded loops containing CG motifs are connected through a double-stranded stem in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…Several studies have shown that TLRs agonists can directly activate NK cells and boost their anti-viral potentials [172174]. One possible candidate is MGN1703, a novel TLR9 agonist currently under clinical testing for the treatment of metastatic colorectal cancer [175178]. Indeed, MGN1703 is able to stimulate plasmacytoid DCs to produce IFN-α that, in turn, increase the expression of NKp46 on NK cells and induce the killing of HIV-1 infected T cell targets [22, 60, 174].…”
Section: Targeting Nk Cells In Hiv-1 Therapymentioning
confidence: 99%
“…Several studies have shown that TLRs agonists can directly activate NK cells and boost their anti-viral potentials [172174]. One possible candidate is MGN1703, a novel TLR9 agonist currently under clinical testing for the treatment of metastatic colorectal cancer [175178]. Indeed, MGN1703 is able to stimulate plasmacytoid DCs to produce IFN-α that, in turn, increase the expression of NKp46 on NK cells and induce the killing of HIV-1 infected T cell targets [22, 60, 174].…”
Section: Targeting Nk Cells In Hiv-1 Therapymentioning
confidence: 99%
“…74,75 CpG ODNs with this structure do not have 75 Induction of these cytokines suggests that MGN1703 has the potential to activate both cellular immunity and humoral immunity. Furthermore, MGN1703 upregulated the expression of human leukocyte antigen D related and intercellular adhesion molecule-1 in B-lineage RPMI-8226 cells.…”
Section: Cpg Odn Nanomedicinesmentioning
confidence: 99%
“…In a recent preclinical study, major liver damage and spleen damage were observed in mice administered a CpG-B ODN (ODN1826). 75 Moreover, in the Phase III clinical trial in which a CpG-B ODN (PF-3512676, also known as ODN2006 or CpG-7909) was combined with standard chemotherapy, it was reported that patients administered with the CpG-B ODN had a high probability of developing adverse events. 114,115 The results of these preclinical and clinical studies suggest that CpG ODNs with a phosphodiester backbone would be preferable to those with a phosphorothioate backbone.…”
Section: Prospects For the Futurementioning
confidence: 99%
“…MGN1703 is a novel, dumbbell-shaped, covalently closed DNA construct, synthesized from nonmodified natural DNA, that we used to agonize TLR9 (7)(8)(9), and we refer to cells activated via this TLR9-triggered pathway as "MGN1703-activated" cells here.…”
mentioning
confidence: 99%